The Implementation of Digital Marketing Strategy at the INACRAFT 2023 - Syafira, Ranisya Yasfiani (UI Scholars Hub, 2025)
Digital marketing or digital marketing is needed by companies to market a product or service using digital media or platforms so that they can cover a wider market with the internet. The use of digital marketing strategies is carried out by many companies, one of the companies that uses digital marketing strategies is PT Mediatama Binakreasi. The final work entitled Digital Marketing Strategy at the Inacraft 2023 Event at PT Mediatama Binakreasi discusses five aspects of strategy including customer engagement, viral marketing, buzz marketing, peer influence, and online community, which are implemented by the Marketing Communication division at PT Mediatama Binacreation. The purpose of this study is to understand the relationship with the five existing aspects, find out the strategy of digital marketing at the INACRAFT event, the effectiveness of digital marketing and how to create content on INACRAFT social media, and also to find out the obstacles in the digital marketing process at the INACRAFT 2023 event. Task Research This Final Work (TKA) uses a qualitative description method, namely by collecting data from direct observation, interviews, and literature studies. The results of the study show that marketing from INACRAFT 2023 uses social media such as Instagram, Facebook, Tiktok, then Websites and also the Paid Ads feature, which is very influential in increasing brand awareness for the INACRAFT 2023 event. It is hoped that this research can help and provide useful information for readers in the field of digital marketing who use social media and Ads features in marketing an event.